Etnography and adrift: options in research - Esposito, Alexandre [UNESP]; Justo, Jose Sterza [UNESP] (Univ Federal Fluminense, Inst Ciencias Sociedade & Desenvolvimento Regional, 2017)
This study aims to examinate and discuss association between adrift technique and etnographic method and its options and reach at scientific investigation turned to issues on urban mobility, such as those involving homeless people and wanderers. In order to that, a general explanation on etnography as a method shall be provided, and on adrift as a technique, by explaining its respective basic concepts with focus on experiences of research at an urban scenario, about options and reach of etnography along with adrift at scientific investigation.
Keywords: Etnography; Research; Methods